2007
DOI: 10.1590/s0034-72992007000600004
|View full text |Cite
|
Sign up to set email alerts
|

Correlação da cadeia ossicular no transoperatório com achados histológicos de colesteatomas

Abstract: Chroni c otitis media is hystopathologycaly defined as the presence of irreversible inflammatory tissue changes in the middle ear. Ossicular lesions represent the most prevalent change. Aim: to correlate the degree of ossicular chain changes seen during surgery with the inflammatory histological degree and the thickness of the cholesteatoma perimatrix. Study design: Cross-sectional study. Methods: Seventyone descriptions of surgeries done in patients submitted to tympanomastoydectomy were reviewed. Cholesteato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Stapes erosion happened in 18 patients (54.5%). These findings differ from the ones from Tos 15 and Dornelles et al 16 who reported incus erosion as the most frequent, followed by the stapes and, later, the malleus.…”
Section: Discussioncontrasting
confidence: 92%
“…Stapes erosion happened in 18 patients (54.5%). These findings differ from the ones from Tos 15 and Dornelles et al 16 who reported incus erosion as the most frequent, followed by the stapes and, later, the malleus.…”
Section: Discussioncontrasting
confidence: 92%